Essential Oils From Citrus unshiu Marc. Effectively Kill Aeromonas hydrophila by Destroying Cell Membrane Integrity, Influencing Cell Potential, and Leaking Intracellular Substances - Zhong, Weiming; Chen, Kangyong; Yang, Linlin; Tang, Tao; Jiang, Sifan; Guo, Jiajing; Gao, Zhipeng (Frontiers in Microbiology, 2022)
Aeromonas hydrophila is one of the important pathogenic bacteria in aquaculture causing serious losses every year. Essential oils are usually used as natural antimicrobial agents to reduce or replace the use of antibiotics. The aim of this study was to evaluate the antibacterial activity and explore the mechanisms of essential oil from satsuma mandarin (Citrus unshiu Marc.) (SMEO) against A. hydrophila. The results of gas chromatography-mass spectrometer demonstrated that SMEO contains 79 chemical components with the highest proportion of limonene (70.22%). SMEO exhibited strong antibacterial activity against A. hydrophila in vitro, the diameter of inhibition zone was 31.22±0.46 mm, the MIC and MBC values were all 1% (V/V). Intracellular material release, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and flow cytometry analysis reveals the dynamic antibacterial process of SMEO, the morphological changes of bacterial cells, and the leakage process of intracellular components. These results demonstrated that SMEO disrupted the extracellular membrane permeability. Our study demonstrated that SEMO has the potential to be used to control and prevent A. hydrophila infections in aquaculture.